209k views
0 votes
Factorise 6^3+11x^2-12x-5
PLEASE ANSWER URGENT

User Duckman
by
5.7k points

1 Answer

2 votes

Answer:

(x - 1)(3x + 1)(2x + 5)

Explanation:

Given

6x³ + 11x² - 12x - 5

The sum of the coefficients = 6 + 11 - 12 - 5 = 0

Hence x = 1 is a root and (x - 1) a factor

Dividing 6x³ + 11x² - 12x - 5 by (x - 1) using Synthetic division

1 | 6 11 - 12 - 5

↓ 6 17 5

-------------------------

6 17 5 0 ← remainder

Quotient = 6x² + 17x + 5

Thus

6x³ + 11x² - 12x - 5 =(x - 1)(6x² + 17x + 5) = (x - 1)(3x + 1)(2x + 5)

User Sachin Bahukhandi
by
5.9k points